A Survey: Internet of Things (IoTs) Technologies, Embedded Systems and Sensors - Tasci, Burak (Springer Science and Business Media Deutschland GmbH, 2024)
The technology known as the Internet of Things, or IoTs, refers to all interconnected computing devices, digital machines, mechanical things, and identifiers that are capable of transferring data across a network without the assistance of humans. Today, IoTs range from small appliances to smart cities. Organizations across various industries are increasingly utilizing IoT technology to enhance their operational efficiency, deliver superior customer service, increase business value, gain deeper customer insights, and enhance their decision-making processes. For this reason, embedded system platforms are used for IoTs solutions developed for different workspaces and applications. In this study, various embedded systems such as Raspberry Pi, ZYNQ, Jetson, Altera Cyclone II, Beagle Bone, Odroid, STM32, PSoC, were investigated, along with IoT communication protocols including IPv6, 6LowPAN, ZigBee, Bluetooth, Wi-Fi, LoRaWAN, Z-Wave, NFC, and Sigfox. Furthermore, a comparative analysis of the sensors utilized in these systems and their respective application areas has been provided. © The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2024.
Keywords: Applıcatıon areas of Iot; Communication protocols; Embedded systems; Internet of things; Sensors